Starvation shrinks the mussel foot secretory glands and impairs the byssal attachment - Zheng, Yi; Yang, Yue-Ming; Xu, Yue-Feng; Wang, Yu-Qing; Shi, Xue; Zheng, Gao-Hai; Li, Yi-Feng (Frontiers in Marine Science, 2022)
Mussel is an economically and ecologically important species widely distributed throughout the world. The mussel adheres to the attachment substrate by secreting byssus external to the body. Various environmental and biological factors influence the process of byssus secretion, and the present study investigated the effect of starvation on byssal secretion in the hard-shelled mussel Mytilus coruscus. Histological changes in mussel foot secretory glands and gene expression of mussel foot proteins were also determined. The experimental setup consisted of starvation treatments for 7, 14 and 21 days, and the control groups. The results showed that the number of produced byssus was higher in the starvation group compared to the CTR group, and the starvation group had a significantly higher of byssal shedding number from 6 days of starvation treatment onwards (p < 0.05). The byssal thread diameter was significantly reduced in all starvation treatment groups (p < 0.05). However, starvation treatment had no effect on the length of the byssal thread (p > 0.05). After 21 days of starvation treatment, the byssal thread volume was significantly lower than that of the CTR group (p < 0.05). A significant decrease in the breaking force of the byssal thread was observed after 14 and 21 days of starvation treatment (p < 0.05), along with an upward shift in the breakpoints. Starvation treatment significantly reduced the percentage of foot secretory glands area to total tissue (p < 0.05). The expression of the mussel foot protein genes (Mcfp-1P and Mcfp-1T) was significantly up-regulated at 7 days of starvation treatment (p < 0.05). These findings reveal that starvation weakens byssal thread performance by influencing mussel foot secretory glands, which increases the dislodgment risks of suspended-cultured mussels.